The pombaline writings about public instruction - Oliveira, Luiz Eduardo; Fonseca, Ana Lúcia Simões Borges (Educar em Revista, 2019)
This article intends to establish a canon of the pombaline writings about public instruction in general, and the teaching of Humanities in particular, which are responsible for what is conventionally called in the educational historiography by the name of pombaline reforms. Additionally, it aims to investigate the way those writings provoked the foundation and affected the development of public instruction in Brazil. To attain such purposes, based on the theoretical support of cultural history and cultural studies, it is used the historiography dedicated to the period, manuscripts and documental, legislative, literary, and epistolary sources, as well as textbooks and periodicals published in the period.